2020
DOI: 10.21203/rs.3.rs-122032/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Roles and Responsibilities of Expert Clients in Adolescent HIV Service Delivery in Eswatini: A Conventional Content Analysis

Abstract: BackgroundLike in other countries throughout sub-Saharan Africa, Eswatini employs a cadre of HIV-positive lay health workers known as expert clients (ECs) for the purpose of mitigating human resource gaps in HIV care. However, there are no insights in the literature describing the scope of their contribution to adolescent-specific HIV service delivery. Therefore, we aimed to elucidate the specific roles and responsibilities of ECs with regard to service delivery among adolescents living with HIV in Eswatini, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This was similarly reported in a published paper from Namibia which described Teen Clubs being limited to meeting in places where physical distancing is possible, with no more than 10 adolescents participating at a time [28]. Prior to the pandemic, Teen Club meetings were also when adolescent participants received ART refills [29][30][31][32]. AHISA teams reported that medication dispensing shifted to localized community-based ART distribution sites to mitigate the need to travel for ART refills during the pandemic.…”
Section: Perceived Individual-level Impactsmentioning
confidence: 69%
“…This was similarly reported in a published paper from Namibia which described Teen Clubs being limited to meeting in places where physical distancing is possible, with no more than 10 adolescents participating at a time [28]. Prior to the pandemic, Teen Club meetings were also when adolescent participants received ART refills [29][30][31][32]. AHISA teams reported that medication dispensing shifted to localized community-based ART distribution sites to mitigate the need to travel for ART refills during the pandemic.…”
Section: Perceived Individual-level Impactsmentioning
confidence: 69%